Characteristics and Influencing Factors of Microbial Community in Heavy Metal Contaminated Soil under Silicon Fertilizer and Biochar Remediation. (6th July 2021) - Zhang, Jiachao; He, Yuewei; Fang, Yingchun; Zhao, Keqi; Wang, Nanyi; Zhou, Yaoyu; Luo, Lin; Yang, Yuan
Abstract : Silicon fertilizer and biochar have been widely used to remediate soil contaminated by heavy metals. The effects and mechanism of silicon fertilizer and biochar addition on the heavy metal availability, soil biological properties, and microbial community characteristics need further study in soils contaminated by heavy metals. Therefore, this research determined how silicon fertilizer, biochar, and their combined using affected microbial communities related with nitrogen and phosphorus cycling. The abundance and composition of the microbial community were evaluated by quantitative PCR and phospholipid fatty acid analysis, respectively. Results showed that silicon fertilizer and biochar addition significantly changed soil properties, including pH, total organic carbon, ammonium, nitrate. The Cd and Zn speciation were significantly reduced by silicon fertilizer, biochar, and their integrated application. Microbial community abundance and structure were also significantly changed. Principal component analysis shows that the difference in soil microbial community structure is the most obvious under the combined addition of biochar, silicon fertilizer and biochar. In addition, the results of fluorescence quantitative PCR showed that with biological addition, the number of soil bacteria was significantly reduced. This study reveals the influence of silicon fertilizer and biochar on bacterial and fungal communities in heavy metal soils and the effect of soil heavy metal availability.